Lexical Noun Variation in the Copy of Cursor Mundi in British Library MS Additional 36983 - Suomalainen, Topi (My University, 2026)
This thesis is a comparative study of the variant lexical nouns that appear in the copy of Cursor Mundi in British Library MS Additional 36983 (commonly known as MS B) when compared against the main text of the Southern Version of Cursor Mundi, which is mainly a copy of Collage of Arms (Herald’s Collage), Arundel Press LVII (commonly known as MS H). The researched material for this thesis was taken from the Southern Version of Cursor Mundi. Thousand-line excerpts were taken at regular intervals a total of six times, and the resulting dataset was searched for lexical noun variation in MS B. Out of a sample size of six thousand lines, 111 instances of noun variation were found. The unique SV nouns and B variants were recorded with data from the OED and compared against each other. The results suggest that the variation was caused by a mix of translation, correction, and scribal mistakes. The conclusion is made that the scribes of MS B did indeed alter the text of their exemplar both intentionally and unintentionally, however this thesis was not able to answer how systematic the process of revision was in MS B. The fact remains that much the manuscript’s unique features have been left unresearched, and this calls for more thorough linguistic investigation into the copy of Cursor Mundi found in MS B.
Keywords: Cursor Mundi; Middle English; historical linguistics; medieval studies; manuscript variation